The influence of Pseudomonas syringae pv. aptata on the functional characteristics of the microgametophyte of beetroot varieties with different levels of resistance to bacteriosis - S. A. Vetrova; E. G. Kozar; K. S. Muhina; I. A. Engalycheva (Овощи России, 2024)
Relevance. An increase in the spread of bacteriosis on beetroot in the conditions of the Moscow region carries an epidemiological danger, which actualizes research on the development of a method-ology for evaluating table beet plants for resistance to bacteriosis in the early stages of ontogenesis. The aim of the research. To identify the nature of the relationship between the reaction of sporophyte and microgametophyte to infection with Pseudomonas syringae pv. aptata (Psa) bacterium of beet-root varieties with different resistance of root crops to bacteriosis.Materials and methods. Objects of research: beetroot plants of the Marusya and Krasny Barhat varietal populations, collection strain Psa 1-21. Using phytopathological methods and methods of gamete breeding, plant resistance was assessed in various variants of infection of sporophyte and gametophyte with suspension and culture filtrate of Psa.Results. The average volume of the affected area of the Psa root crops of the Marusya variety was 3.5 times greater than that of the Krasny Barhat variety (Vp = 53 mm3), which is characterized by alignment and absence of susceptible forms (Vp >300 mm3). The Marusya variety has a wide intrapopulation polymorphism in the stability of root crops and leaves, where most genotypes showed medium or high susceptibility to the pathogen. Both varieties showed an increase of 10-30% relative to the control of pollen viability at high (CFU 12*108 cl/ml) and low (CFU 2.4*108 cl/ml) concentrations of the pathogen. The positive effect of Psaon the growth of pollen tubes was noted: in the Marusya variety, as the concentration increased, the stimulating effect increased, in the Krasny Barhat variety, it gradually decreased. When adding a 2.5-fold diluted Psa culture filtrate, the susceptible Marusya variety showed an increase in pollen viability (by 3%), and the resistant Krasny Barhat variety showed a 24% decrease relative to the control. According to the growth rate of the pollen tube, the 4:6 dilution was also differentiating, where the average length of the tubes of the susceptible variety exceeded the control by 10%, and in the stable variety it was 18% lower than the control variant.Conclusion. An inverse relationship was revealed between the resistance of sporophyte to Psa and changes in the functional parameters of the microgametophyte of beetroot varieties Marusya and Krasny Barhat under the influence of a phytopathogen. The results obtained indicate the prospects for the development of a methodology for the selection of bacteriosis-resistant genotypes of beetroot by the reaction of microgametophyte.